"Change It, Change It" Barriers for Parent-Adolescent Communication about Contraceptives in Bahir Dar City, North West, Ethiopia, 2023 - Bethilhem Wubet; Taye Zeru; Gizachew Worku; Gedefaw Abeje (Hindawi Limited, 2024)
Background. The rising prevalence of risky behavior among East African adolescents places an additional strain on them, their families, and society. Adolescents in this area are particularly vulnerable to sexual and reproductive health (SRH) issues such as sexually transmitted infections, unexpected pregnancies, unsafe abortions, sexual abuse, and rape. This is believed to be due to the lack of communication between most parents in this region and their adolescents about SRH issues, such as contraceptives. This study explored barriers to parent-adolescent communication about contraceptives. Materials and Methods. A qualitative study with a phenomenological approach was used. Participants in the study were purposefully selected parents and adolescents who lived in the city of Bahir Dar, Ethiopia. An in-depth interview guide was prepared and used to collect the data. ATLAS.ti software was used for coding, and thematic analysis was subsequently performed. Results. Thirty adolescents and 20 parents participated in the in-depth interviews. Five main themes and 14 subthemes were identified. The main barriers to parental-adolescent communication about contraceptives were cultural and religious factors, the knowledge gap, parents' busyness, age, and the media as a source of information. Conclusions and Recommendations. To improve communication with very young adolescents (ages 10-13), parents should have sufficient and accurate knowledge about contraception as well as efficient communication techniques. To involve all stakeholders, including parents, in the deconstruction of sociocultural norms surrounding the SRH of adolescents, it is important to strengthen and spread campaigns that raise awareness of parental-adolescent communication.